(E)-Ethyl 4-[4-(diethylamino)styryl]benzoate - Yong-Yan Yao; Long Lv; Jun-Xiang Zhang; Hong-Wu He (Acta Crystallographica Section E, 2008)
In the title molecule, C21H25NO2, the dihedral angle between the two benzene rings is 4.8 (2)°. Both the ethyl group of the ester group and one of the ethyl groups attached to the N atom are disordered over two sites, the approximate occupancies being 66:34 and 81:19, respectively. In the cystal structure, there are no direction-specific interactions.